Implementation of Least Significant Bit Steganography with Caesar Cipher Layout Dvorak web-based - Ridhwan Nadif Kurnia; Al Diras Pradiptha; Muhammad Fajar Jati Permana; Kimberly Alfa Dipradja; Rizki Afrizal; Deden Pradeka; Zahra Khaerunnisa (Jurnal Simantec, 2025)
Secure data communication is an essential requirement in the digital age, especially in the exchange of confidential information. One of the main problems is the potential for eavesdropping by unauthorised parties who can access open messages. To overcome this, this research aims to develop a website-based system that combines the Least Significant Bit (LSB) method steganography technique and the Caesar cipher method cryptography with the Dvorak keyboard layout to increase data security. The research method used is prototype method with the stages of concept formulation, prototype design, and continuous evaluation. The system was tested by inserting the word ‘TEKKOM’ into a digital image and measuring the quality using Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR). The test results show an MSE value of 0.0001466049 and PSNR of 86.47 dB, which means that the visual quality of the image does not decrease significantly and the message is successfully inserted and extracted without errors. The Dvorak keyboard layout adds a layer of security through uncommon input patterns, making it difficult for outsiders to analyse. Thus, the system is able to provide a secure, efficient, and practical solution for web-based information hiding without the need for a database and is still user-friendly.Keywords: Dvorak, Steganography, Caesar Cipher, Least Significant Bit, Website